2009
DOI: 10.3168/jds.2009-2081
|View full text |Cite
|
Sign up to set email alerts
|

Hot topic: Pathway confirmed for the transmission of melamine from feed to cow's milk

Abstract: Eight lactating Holstein cows were randomly allotted to 2 groups in a trial to establish whether a pathway exists for the transmission of melamine from feed to milk. All cows received oat hay ad libitum and 15 kg of concentrate pellets per cow daily. The concentrate pellets contained either melamine-contaminated corn gluten meal of Chinese origin (melamine treatment) or locally produced melamine-free corn gluten meal (control treatment). Cows in the melamine treatment ingested 17.1 g of melamine per day. Cows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
25
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 2 publications
15
25
1
2
Order By: Relevance
“…Melamine in eggs Different authors reported an indirect melamine contamination of animal products, such as milk, cheese, meat and eggs, when animals were exposed to melamine-contaminated diets (Cruywagen et al, 2009;Dong et al, 2010;Cruywagen et al, 2011;Sun et al, 2011). The existence of an excretion pattern from feed to eggs was also reported (Bai et al, 2010;Chen et al, 2010;Dong et al, 2010;Valat et al, 2011;Yang et al, 2011).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Melamine in eggs Different authors reported an indirect melamine contamination of animal products, such as milk, cheese, meat and eggs, when animals were exposed to melamine-contaminated diets (Cruywagen et al, 2009;Dong et al, 2010;Cruywagen et al, 2011;Sun et al, 2011). The existence of an excretion pattern from feed to eggs was also reported (Bai et al, 2010;Chen et al, 2010;Dong et al, 2010;Valat et al, 2011;Yang et al, 2011).…”
Section: Resultsmentioning
confidence: 97%
“…Some authors have recently suggested that melamine contamination in milk could be not only related to direct adulteration but also to the presence of melamine in feeds for lactating dairy cows, because of the fact that a passage of melamine from feed to milk and milk products was reported (Cruywagen et al, 2009;Battaglia et al, 2010;Shen et al, 2010;Sun et al, 2011;Zheng et al, 2011). In addition, a carryover of melamine from feed to egg and body tissues of laying hens has been reported by different authors (Bai et al, 2010;Chen et al, 2010;Dong et al, 2010;Valat et al, 2011;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nephrotoxicosis in Iberian piglets subsequent to exposure to melamine and derivatives in Spain between 2003 and 2006, [10] and the transmission of melamine from feed to cow's milk has been recently demonstrated [8]. These outbreaks emphasize that feedstuffs remain vulnerable to chemical contamination and an increase of surveillance on raw material and animal feed production at EU level is strongly recommended.…”
Section: A) Alt Alanine Aminotransferase (B) Tbil Total Bilirubimentioning
confidence: 99%
“…Melamine appeared in the milk within 8 hr following the first feeding and reached a plateau value of approximately 15 mg/kg milk at 56 h. Upon cessation of exposure, milk melamine levels initially declined rapidly (by 39 % at 8 hrs and by 85 % at 32 hrs post exposure) but fell below the detection limit (5 μg/kg of milk) only after 6 days. Apart from normal daily variation, milk yield remained constant during the experiment at approximately 25 kg per day Average total melamine excretion via the milk can be calculated at 15 × 25 = 375 mg per day, during steady-state (Cruywagen et al, 2009). From these data a steady state transfer of 375 / 17.13 = 22 mg melamine in milk per gram melamine in the feed (2.2 %) can be EFSA Journal 2010; 8(4):1573 calculated.…”
Section: Humansmentioning
confidence: 99%
“…Although melamine has been found in tissues and in milk of several species (for overview see Tolleson et al, 2009), only one systematic study seems to have been published in which carry-over of melamine to milk has been examined. Cruywagen et al (2009) dosed dairy cows with (nominally) 17.13 g of melamine per day via the feed. The substance was given in 15 kg of a pelleted feed supplement, which contained 1142 mg melamine/kg.…”
Section: Humansmentioning
confidence: 99%